Evolutionary Conservation and Diversification of Rh Family Genes and Proteins - Huang, Cheng-Han; Jianbin Peng (Proceedings of the National Academy of Sciences - PNAS, 2005)
Rhesus (Rh) proteins were first identified in human erythroid cells and recently in other tissues. Like ammonia transporter (Amt) proteins, their only homologues, Rh proteins have the 12 transmembrane-spanning segments characteristic of transporters. Many think Rh and Amt proteins transport the same substrate, $NH_3/NH_4^+$, whereas others think that Rh proteins transport CO2 and Amt proteins NH3. In the latter view, Rh and Amt are different biological gas channels. To reconstruct the phytogeny of the Rh family and study its coexistence with and relationship to Amt in depth, we analyzed 111 Rh genes and 260 Amt genes. Although Rh and Amt are found together in organisms as diverse as unicellular eukaryotes and sea squirts, Rh genes apparently arose later, because they are rare in prokaryotes. However, Rh genes are prominent in vertebrates, in which Amt genes disappear. In organisms with both types of genes, Rh had apparently diverged away from Amt rapidly and then evolved slowly over a long period. Functionally divergent amino acid sites are clustered in transmembrane segments and around the gas-conducting lumen recently identified in Escherichia coli AmtB, in agreement with Rh proteins having new substrate specificity. Despite gene duplications and mutations, the Rh paralogous groups all have apparently been subject to strong purifying selection indicating functional conservation. Genes encoding the classical Rh proteins in mammalian red cells show higher nucleotide substitution rates at nonsynonymous codon positions than other Rh genes, a finding that suggests a possible role for these proteins in red cell morphogenetic evolution.